The Importance of Carbon Dioxide Gas in All Life Processes (Eurasian Journal of Engineering and Technology, 2023)
The normal functioning of vital processes in all living organisms depends on the amount of carbon dioxide in the human bloodstream. Carbonic anhydride increases the body's resistance to bacterial and viral infections, is important in the metabolism of biologically active substances, that is, in the processes of assimilation and dissimilation. Carbon dioxide is a part of nature and is necessary for many physical and chemical processes. For example, if it did not have the ability to retain heat, the greenhouse effect, which maintains a constant temperature throughout the planet, could not occur. This article discusses the use and importance of carbon dioxide as a chemical raw material. CO2 gas is not only a polluting gas but also a valuable chemical and a major source of carbon. In addition, carbon dioxide gas is also required for photosynthesis of plants. It is a process in which carbon dioxide is exchanged to release oxygen. This oxygen is necessary for breathing and the realization of life on the planet